The investigation of auto-ignition properties of 1-butanol–biodiesel blends under various temperatures conditions. (15th August 2023) - Kuszewski, Hubert; Jaworski, Artur; Mądziel, Maksymilian; Woś, Paweł
Highlights: CVCC method was used in the investigation. Derived cetane numbers for RME and 1-butanol were determined. Ignition and combustion delay for 1-butanol–biodiesel blends were measured. Tests of auto-ignition were realized for different combustion chamber temperatures. Abstract: In this article, the auto-ignition properties of blends of high cetane rape methyl esters (RME) as biodiesel and 1-butanol were investigated, with 1-butanol fractions of up to 25% by volume. The tests were performed using the constant volume combustion chamber (CVCC) method to determine the combustion chamber temperature effect (between 550 °C and 650 °C) on the ignition delay (ID) and combustion delay (CD) periods of the verified blends. The research of the auto-ignition properties was complemented with the derived cetane number (DCN) and the calorific properties of the fuels tested. The results uncovered several properties relating to such blends and also showed that the periods of ID and CD increase with an increase in the 1-butanol fraction in the 1-butanol–biodiesel fuel blend (1-BBF). The work also shows that an increase in the temperature of the combustion chamber into which the fuel is supplied causes delay periods to shorten to varying degrees. For fractions of 5–25% by volume in 1-butanol, for each addition of a 5% fraction of 1-butanol, the cetane number for 1-BBF decreases by an average of 4.2 units.